ETNOMATEMATIKA TENUN TRADISIONAL BUNA TIMOR TENGAH UTARA DAN IMPLIKASI PEDAGOGIS - Selestina Nahak; Ivonia Ulu; Yohanes Jefrianus Kehi (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
Abstract This study aims to reveal the mathematical concepts embedded in the weaving activities of Buna woven-cloth artisans in Letmafo Village, Central Insana District, North Central Timor Regency. This research employed a qualitative ethnographic approach. Data were collected through observation, interviews, and documentation with three main informants: a traditional leader and two experienced weavers. Data analysis used domain, taxonomy, componential, and cultural-theme stages. The findings show that weaving activities contain mathematical elements such as counting (the number of threads and repeated patterns), measuring (length and width of the cloth using non-standard units such as hand-span), and designing (forming geometric patterns such as squares, triangles, rhombuses, and lines of symmetry). Ethnomathematics in the Buna motif reflects an integration between local culture and mathematical concepts of geometry and number patterns that can be used as contextual learning resources. Keyword: Ethnomathematics, Buna woven cloth, Letmafo culture, mathematics learning